Sistem Monitoring Kelembaban Tanah dan Kendali Pompa Air Menggunakan Arduino dan Internet - Nadzif, Husnun; Andrasto, Tatyantoro; Aprilian, Selamet (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2019)
Cultivation of eggplant plants requires special conditions, specifically with soil moisture about 80% - 90%. Factors that affect soil moisture on plant growth is water necessary. To meet the water necessary and keep the soil moisture can be done with watering the plants. Currently, the cultivation technique of eggplant is watered manually, then needed a system that is able to monitor of soil moisture and control waterpump to water the plants automatically so that soil moisture conditions can be maintained. This system uses Arduino as microcontroller, YL-69 soil moisture sensor, SIM800L GSM module as data transmission, waterpump as sprinkler, and website as interface of the system because has advantage and convenience on the operation. The research method used the method of Research and Development. Test is done with Black Box test, Sensor Calibration test, and performance of the system test. Black Box test results indicate the functions in the website can be run properly, the sensor calibration test results indicate an average error of 2,2%, and the performance testing system obtained percentage success of 100%.